Supermarkets’ Governance of the Agri-food Supply Chain: Is the ‘Corporate-Environmental’ Food Regime Evident in Australia? - Smith, Kiah; Lawrence , Geoffrey; Richards, Carol (The International Journal of Sociology of Agriculture and Food, 2010)
This article investigates the extent to which the purported greening of food retailing and consumption in Australia is consistent with the development of a corporate-environmental food regime. Recent developments in food regime theory, particularly the concept of an emerging third food regime (the so-called ‘corporate-environmental food regime’), provide a useful organizing framework for understanding recent agri-restructuring trends. We find that, while a globally based, third food regime is becoming more apparent, the attributes that relate to corporate retail-driven greening of the supply chain are less evident within Australia’s domestic market than in its EU counterparts. However, there is some evidence that Australia’s export market is subject to some degree of ‘greening at a distance’ due to private regulations imposed by supermarkets overseas. We argue that while broader agri-restructuring trends may be evident at an international level, elements of greening specific to national contexts are important for determining the trajectory of any third food regime.